Legal Protection of Victims of Domestic Violence in the Perspective of Viktimology and Criminal Law - Odi Sanjaya; Jodi Prianus (Yayasan Cinta Negara, 2025)
This research explores the legal protection of victims of domestic violence through the lens of victimology and criminal law. Domestic violence remains a pervasive issue in many societies, including Indonesia, with far-reaching psychological, physical, and social consequences for victims. Although various legal instruments, such as Law No. 23 of 2004 on the Elimination of Domestic Violence, have been enacted to provide legal remedies and protection for victims, challenges in implementation persist. This study examines how the principles of victimology can complement criminal law frameworks to ensure more comprehensive protection for victims. It highlights the importance of recognizing victims not only as passive sufferers but as subjects entitled to rights, including legal aid, psychological support, restitution, and participation in legal processes. Using a normative-empirical method, this study analyzes the legal provisions alongside field data obtained through interviews and case studies. The findings reveal gaps between legal norms and practical enforcement, often due to lack of awareness, institutional limitations, and cultural factors. Therefore, the research emphasizes the need for stronger inter-institutional coordination, enhanced victim services, and reforms in legal procedures to ensure justice and recovery for victims. This integrated approach aims to support a more humane and victim-centered justice system